1996
DOI: 10.1523/jneurosci.16-19-06146.1996
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cell Migration from the Lateral Ganglionic Eminence in the Rat

Abstract: From previous developmental studies, it has been proposed that the neurons of the ventrolateral cortex, including the primary olfactory cortex, differentiate from progenitor cells in the lateral ganglionic eminence. The objective of the present study was to test this hypothesis. The cells first generated in the forebrain of the rat migrate to the surface of the telencephalic vesicle by embryonic day (E) 12. Using [3 H]thymidine, we found that most of these cells contributed to the formation of the deep layer I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
232
4
9

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(261 citation statements)
references
References 65 publications
16
232
4
9
Order By: Relevance
“…Previous studies indicated that the majority of olfactory cortex neurons are derived from the ventral pallium, in which Pax6 is strongly expressed during embryogenesis, and that the Pax6 mutant lacks subpopulation of these neurons (de Carlos et al 1996;Yun et al 2001;Hirata et al 2002). We also reported that neurons in the superficial layer of the olfactory cortex are deficient in the Pax6 mutant .…”
Section: Role Of Pax6 In the Developing Olfactory Cortexsupporting
confidence: 62%
“…Previous studies indicated that the majority of olfactory cortex neurons are derived from the ventral pallium, in which Pax6 is strongly expressed during embryogenesis, and that the Pax6 mutant lacks subpopulation of these neurons (de Carlos et al 1996;Yun et al 2001;Hirata et al 2002). We also reported that neurons in the superficial layer of the olfactory cortex are deficient in the Pax6 mutant .…”
Section: Role Of Pax6 In the Developing Olfactory Cortexsupporting
confidence: 62%
“…The direction of endothelial cell migration resembles tangential migration of GABA neurons, but the endothelial cell migration begins earlier 18,19 . Neurogenesis and GABA neuron migration are regulated by region-specific homeobox transcription factors, which bestow cell-autonomous regional identities 7,20,21 .…”
Section: Endothelial Cells Express Homeobox Transcription Factorsmentioning
confidence: 96%
“…However, GABA neurons of the basal forebrain are not restricted to the compartment of origin but migrate across compartmental boundaries 18,19 , despite expressing compartment-specific homeobox genes 29 . Which of these two models applies to telencephalic endothelial cells?…”
Section: Endothelial Cells Express Homeobox Transcription Factorsmentioning
confidence: 99%
“…Unlike pyramidal neurons, which are born in the dorsal telencephalon, the majority of cortical interneurons in mice are generated in the medial ganglionic eminence (MGE) of the ventral forebrain, between embryonic day 12.5 (E12.5) and birth, and reach the cortex by tangential migration (de Carlos et al, 1996;Anderson et al, 1997;Tamamaki et al, 1997;Lavdas et al, 1999;Sussel et al, 1999;Wichterle et al, 1999;Pleasure et al, 2000;Marin and Rubenstein, 2003;Valcanis and Tan, 2003). The first population of interneurons emerging from the MGE (ϳE12.5) invade the cortex via the marginal zone (MZ), whereas subsequent waves of GABAergic interneurons populate the lower intermediate and subventricular zones (IZ/SVZ) (Corbin et al, 2001;Jimenez et al, 2002;Marin and Rubenstein, 2003;Tanaka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%